Rahmad Pemanfaatan Media Pembelajaran Pengenalan Organ Lambung Berbasis Augemented Reality (AR) Untuk Program Studi DIII Keperawatan Universitas 'Aisyiyah Surakarta - Rahmad Ar dhani; Ita Permatahati; Aisyah Mutia Dawis (Universitas PGRI Yogyakarta, 2022)
Learning media is a modern technology that can be used between educators and students in learning and teaching activities that can connect, convey information and channel messages so as to create effective and efficient teaching and learning activities. Learning media can make communication happen between educators and students in the learning process. If in teaching and learning activities do not use the media then the learning process will not occur. Currently, the development of technology is very rapid. Learning media is currently following technological developments. One of the learning media that follows technological developments is learning media based on augmented reality. AR (augmented reality), is a technology that combines two-dimensional and or three-dimensional virtual objects into a real environment and then projects these virtual objects in reality in real time. Augmented reality applies to all senses, including hearing, touch, and smell. Apart from being used in fields such as health, the military, the manufacturing industry and the world of education. This AR technology can insert certain information into the virtual world and display it in the real world with the help of equipment such as webcams, computers, Android cellphones, or special glasses. AR learning media can visualize a gastric organ visually for understanding and the structure of an object model enabling AR to be a more effective medium according to the objectives of the learning media. This study aims to: (1) design and build Augmented Reality learning media on gastric organs; (2) knowing the performance and feasibility of Augmented Reality as a learning medium. Researchers used the experimental method and collected the results of observations. The purpose of making this learning media is to introduce the heart organ in the DIII Nursing Study Program, 'Aisyiyah University, Surakarta. Keywords: Augmented Reality, Learning Media, Stomach Organs.